Comparison Between Neurally Adjusted Ventilatory Assist and Pressure Support Ventilation Levels in Terms of Respiratory Effort. Issue 3 (March 2016) - Carteaux, Guillaume; Córdoba-Izquierdo, Ana; Lyazidi, Aissam; Heunks, Leo; Thille, Arnaud W.; Brochard, Laurent
Abstract : Objectives: To understand the potential equivalence between neurally adjusted ventilatory assist and pressure support ventilation levels in terms of respiratory muscle unloading. To compare the respiratory pattern, variability, synchronization, and neuromuscular coupling within comparable ranges of assistance. Design: Prospective single-center physiologic study. Setting: A 13-bed university medical ICU. Patients: Eleven patients recovering from respiratory failure. Interventions: The following levels of assistance were consecutively applied in a random order: neurally adjusted ventilatory assist levels: 0.5, 1, 1.5, 2, 2.5, 3, 4, 5, and 7 cm H2 O/μvolt; pressure support levels: 7, 10, 15, 20, and 25 cm H2 O. Measurements and Main Results: Flow, airway pressure, esophageal pressures, and peak electrical activity of the diaphragm were continuously recorded. Breathing effort was calculated. To express the percentage of assist assumed by the ventilator, the total pressure including muscular and ventilator pressure was calculated. The median percentage of assist ranged from 33% (24–47%) to 82% (72–90%) between pressure support 7 and 25 cm H2 O. Similar levels of unloading were observed for neurally adjusted ventilatory assist levels from 0.5 cm H2 O/μvolt (46% [40–51%]) to 2.5 cm H2 O/μvolt (80% [74–84%]). Tidal variability was higher during neurally adjusted ventilatory assist and ineffective efforts appeared only in pressure support. In neurally adjusted ventilatory assist, double triggering occurred sometimes when electrical activity of the diaphragm signal depicted a biphasic aspect, and an abnormal oscillatory pattern was frequently observed from 4 cm H2 O/μvolt. For both modes, the relationship between peak electrical activity of the diaphragm and muscle pressure depicted a curvilinear profile. Conclusions: In patients recovering from acute respiratory failure, levels of neurally adjusted ventilatory assist between 0.5 and 2.5 cm H2 O/μvolt are comparable to pressure support levels ranging from 7 to 25 cm H2 O in terms of respiratory muscle unloading. Neurally adjusted ventilatory assist provides better patient-ventilator interactions but can be sometimes excessively sensitive to electrical activity of the diaphragm in terms of triggering. Abstract : Supplemental Digital Content is available in the text.